2008
DOI: 10.1165/rcmb.2007-0440oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Epithelial Cells Express a Functional Cold-Sensing TRPM8 Variant

Abstract: Several transient receptor potential (TRP) ion channels sense and respond to changes in ambient temperature. Chemical agonists of TRP channels, including menthol and capsaicin, also elicit sensations of temperature change. TRPM8 is a cold-and menthol-sensing ion channel that converts thermal and chemical stimuli into neuronal signals and sensations of cooling/cold. However, the expression and function of TRPM8 receptors in non-neuronal cells and tissues is a relatively unexplored area. Results presented here d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
102
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 42 publications
7
102
0
3
Order By: Relevance
“…At least three short TRPM8 isoforms, each exhibiting their own pathophysiological functions, have been reported in previous studies. Sabnis et al (6) reported that the full-length TRPM8 transcript was absent in human lung epithelial cells and identified a novel truncated TRPM8 variant that was selectively expressed as a modulator of respiratory physiology in cold air. Furthermore, Bidaux et al (8) reported the following two novel short splice variants of TRPM8, which were cloned from prostate cancer cells, using a model of HEK293 cells: sM8α and sM8β.…”
Section: Discussionmentioning
confidence: 99%
“…At least three short TRPM8 isoforms, each exhibiting their own pathophysiological functions, have been reported in previous studies. Sabnis et al (6) reported that the full-length TRPM8 transcript was absent in human lung epithelial cells and identified a novel truncated TRPM8 variant that was selectively expressed as a modulator of respiratory physiology in cold air. Furthermore, Bidaux et al (8) reported the following two novel short splice variants of TRPM8, which were cloned from prostate cancer cells, using a model of HEK293 cells: sM8α and sM8β.…”
Section: Discussionmentioning
confidence: 99%
“…The TRPM8 protein is expressed in various tissues, including the brain, sensory neurons, lungs, heart, and, notably, the prostate (6,7). Although the role of TRPM8 as the cold and menthol receptor has been well established in the peripheral nervous system (8 -10), its role in other tissues is not well understood because no endogenous agonists of TRPM8 have been identified thus far.…”
mentioning
confidence: 99%
“…TRPA1 and TRPV1, as well as other TRP channels, are expressed by various airway epithelial and alveolar cells in addition to airway neurons. Activation of TRPA1 (10,11), TRPV1 (7,(12)(13)(14)(15)(16)(17), TRPV4 (18), and transient receptor potential cation channel, subfamily M, member 8 (TRPM8) (19) in these cell types by prototypical agonists, select environmental pollutants, and PM also has been demonstrated to cause proinflammatory cytokine/chemokine production and, in some cases, apoptosis.…”
mentioning
confidence: 99%